FHM presents ... the biggest book of bar-room jokes. (Prion Books Limited, 2009)
A huge joke book, this isn't some simple crammed-full-of-crap tome like the others that you see on a display table gathering dust and getting creased. The Biggest Book of Bar-Room Jokes is a collection of the funniest jokes ever to be put together all in the same place at one time! Fantastic FHM illustrations complement the jokes perfectly, all adding together to make this the most important joke book of our time.